Alopecia Areata and Medical Modulation of the Intrinsic Property of Melanin to Transform Light Into Chemical Energy Through the Water Dissociation - Herrera, Arturo Solis; Solis-Arias, Martha Patricia; Tarasov, Vadim V.; Ashraf, Ghulam Md; Aliev, Gjumrakch (Archives of Clinical and Biomedical Research, 2017)
Background: Alopecia areata is one of the most common autoimmune diseases. The pathobiology of this chronic, relapsing hair-loss disorder is not fully understood, and the available therapies are disappointing. Objective: Currently considered a T-cell-mediated autoimmune disease, in which the gradual loss of protection provided by immune privilege of the normal hair follicle plays an important role. It is associated with an increased overall risk of other autoimmune disease in approximately 16% patients, being the most frequent autoimmune thyroid disease in 8 to 28 % patients, followed by vitiligo in 4 % patients, and lupus erythematosus in 0.6 % patients. Methods: In this case report, we show a female patient treated with QIAPI 1 (120698). Results: We have found that an enhancer of the process of generation and distribution of energy that comes from melanin, with encouraging results. Conclusions: This is first report indicates that the Melanin in its role as a generator of energy opens a new landscape in relation to the study and treatment of autoimmune disorders like alopecia areata.